2017
DOI: 10.1002/2017gl073570
|View full text |Cite
|
Sign up to set email alerts
|

GPS Signal Corruption by the Discrete Aurora: Precise Measurements From the Mahali Experiment

Abstract: Measurements from a dense network of GPS receivers have been used to clarify the relationship between substorm auroras and GPS signal corruption as manifested by loss of lock on the received signal. A network of nine receivers was deployed along roadways near the Poker Flat Research Range in central Alaska, with receiver spacing between 15 and 30 km. Instances of large‐amplitude phase fluctuations and signal loss of lock were registered in space and time with auroral forms associated with a sequence of westwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…The scintillation event described in this case study was determined to be due to the F-region based on all-sky images of emissions also. Another case study from the literature demonstrates E-region phase-only scintillation on 7 October 2015 (Mrak et al, 2018;Semeter et al, 2017). That study recorded array-wide loss of lock on multiple GPS signals associated with ionospheric scintillation.…”
Section: Radio Sciencementioning
confidence: 94%
See 3 more Smart Citations
“…The scintillation event described in this case study was determined to be due to the F-region based on all-sky images of emissions also. Another case study from the literature demonstrates E-region phase-only scintillation on 7 October 2015 (Mrak et al, 2018;Semeter et al, 2017). That study recorded array-wide loss of lock on multiple GPS signals associated with ionospheric scintillation.…”
Section: Radio Sciencementioning
confidence: 94%
“…We use two case studies in the literature (Semeter et al, ; Su, Datta‐Barua, et al, ) to help determine which PFISR data parameter, density, or ion or electron temperature, is a reasonable single indicator of the layer correlated with the GPS scintillations. The first case study from the literature is an F‐region scintillation on 8 December 2013 (Datta‐Barua et al, ; Su, Datta‐Barua, et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With recent advances in imaging technology, the physical morphology of aurora can now be studied in more detail from microscopic to macroscopic sizes using digital All Sky Imagers (ASIs; Donovan et al, ; Mende et al, ). Previous observational studies (e.g., Basu et al, ; Jin et al, ; Kinrade et al, , ; Pi et al, ; Prikryl et al, ; Semeter et al, ; Van der Meeren et al, ) have demonstrated that auroral precipitation can create electron density structures in the ionosphere and a radio signal traversing through these irregularities can experience rapid amplitude and phase fluctuations called scintillation. Scintillation can sometimes cause receivers to lose lock on a radio signal and hence can affect the accuracy of Global Navigation Satellite Systems (GNSS), including GPS (e.g., Garner et al, ; Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%